Representasi Perdagangan Manusia Dalam Film “Cross The Line” (Analisis Roland Barthez) - Akhmad Ibnu Fadhilla; Priatna (CV Edujavare Publishing, 2024)
Movies function as mass media that represent reality in society. For example, the issue of human trafficking that often occurs is told in the movie